Pengaruh Gender, Kompensasi, Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan(Studi Empiris Pada Karyawan Bagian Akuntansi PT. Solo Murni) - Nurdiana, Rosalina, Dra. Rina Trisnawati, M.Si. Ak.,Ph.D.CA (2016)
This study aims to determine the effect of gender , compensation, work motivation, and work environment to employee performance empirical studi in accounting departement PT. Solo Murni. The sampling method using saturated sample. Total of respondents who participated in this study is 45 employees. Data analisys using multiple linear regression analyswith SPSS 21. The results of this study indicate of gender, compensation, work motivation, and work environment have an effect to employee performance. Keywords : gender, compensation, work motivation, work environment and employee performance